Detection and Analysis of Harmful Algal Blooms and Fish Mortalities in Jakarta Bay Via Satellite Imagery - Tumpak Sidabutar; Endang S. Srimariana; H.A.W Cappenberg; S. Wouthuyzen (Scientific Research, New Technologies and Applications Vol. 5, 2024)
The coastal region of Jakarta Bay is susceptible to fish mortality and harmful algal blooms (HAB), often triggered by human activities and environmental changes. This study analyzed data from the Terra and Aqua MODIS satellites collected between 2004 and 2015 to measure chlorophyll-a levels indicative of algal blooms. The research aimed to identify and examine fish mortality and HAB in Jakarta Bay using satellite imagery. Multispectral and hyperspectral satellite data were processed to detect harmful algae distribution and fish mortality regions, integrating field data, biological water parameters, and remote sensing data. The findings suggest satellite imagery effectively monitors chlorophyll-a concentration variations, which is crucial for HAB detection. However, severe blooms do not always result in significant fish deaths. The primary cause of fish mortality was insufficient water circulation, which led to oxygen deficiency during peak blooms. The study highlights the potential of satellite-based monitoring for identifying and managing toxic algal blooms and fish deaths, providing essential data for water resource management in Jakarta Bay. Despite limitations like cloud cover, developing an early warning system (EWS) using satellite imagery is proposed as a revolutionary solution for algal blooms. This technique is vital for establishing an EWS in Jakarta Bay.